# Simplify the expression √96/8?

Simplify the expression √96/8

A.4√3

___

√2

B.√2

___

4

C. 2√3

D. 1

___

2√3

2. What is the value of j in the equation √j + √j + 14 = 3√j +10 ?

A. 2

B. 4

C. 16

D. √2

• amin_226
1 month ago

1.

C. √96/8 = √12 = √(4)(3)= (√4)(√3)= 2√3

2.

√j + √j + 14 = 3√j +10 thus 2√j + 14 = 3√j + 10

then

14 – 10 = 3√j -2√j so √j = 4 then (√j )^2 = 4^2 thus j= 16

1 month ago

1. is that sqrt(96/8) or sqrt(96)/8 ?

sqrt(96/8) = sqrt(12) = sqrt(4*3) = sqrt(4)*sqrt(3) = 2*sqrt(3) {so your multiple choice answer of C is the answer.}

sqrt(96)/8 = sqrt(16*6)/8 = [sqrt(16)*sqrt(6)]/8 = [4*sqrt(6)]/8 = sqrt(6)/2

2. sqrt(j) + sqrt(j) + 14 = 3*sqrt(j) + 10

We can add/subract/multiply/divide by the same amount to both sides of an equals equation and still maintain the equality. We want to solve for the unknown variable, in this case j, by isolating it all by itself on one side of the equation and multiplied only by 1.

sqrt(j) + sqrt(j) + 14 = 3*sqrt(j) + 10

2*sqrt(j) + 14 = 3*sqrt(j) + 10

2*sqrt(j) + 14 – 10 = 3*sqrt(j) + 10 – 10

2*sqrt(j) + 4 = 3*sqrt(j)

2*sqrt(j) + 4 – 2*sqrt(j) = 3*sqrt(j) – 2*sqrt(j)

4 = sqrt(j)

multiply the equation by itself:

4^2 = [sqrt(j)]^2

4*4 = sqrt(j)*sqrt(j)

16 = j

(to double-check, plug in 16 for j into the original equation:

sqrt(j) + sqrt(j) + 14 = 3*sqrt(j) + 10

sqrt(16) + sqrt(16) + 14 ?= 3*sqrt(16) + 10

4 + 4 + 14 ?= 3*4 + 10

8 + 14 ?= 12 + 10

22 = 22

• Anonymous
1 month ago

1. C sqrt(96/8) = sqrt(12) = sqrt(4*3) = sqrt4 * sqrt3 = 2*sqrt3

2. C simplify to 2sqrt(j) + 14 = 3sqrt(j) +10

…then 4 = sqrt(j)

…then square each side to get 16 = j

• PrincessL
1 month ago

√(96/8) = √12 = √4√3 = 2√3